Pengembangan Media Pembelajaran Interaktif Menggunakan Quizizz Dalam Mata Pelajaran PAI di Rumah Belajar Raudhatul Huffaz Untuk Meningkatkan Hasil Belajar Siswa - Musthofa, Azka; Hafidz, Hafidz (Journal of Comprehensive Science, 2025)
The quality of the learning process is often hampered by teaching methods that lack variety and fail to engage students, particularly in Islamic Religious Education (PAI). This study focuses on the development and evaluation of interactive learning media based on Quizizz as an effort to improve student learning outcomes at Raudhatul Huffaz Learning House. The research methodology employed is Research and Development (R&D) following the ADDIE model (Analysis, Design, Development, Implementation, Evaluate). Data were collected through observation, documentation studies, and questionnaires. Research participants included 39 general students from Raudhatul Huffaz Learning House taking PAI subjects. Expert validation results indicate that the Quizizz learning media is highly suitable and practical. Assessments from media experts yielded an average of 3.7, while material experts gave an average of 4.0, both signifying "very practical" criteria. Trials on a small group (5 students) showed a student response rate of 90% with an "excellent" category. Subsequently, trials on a large group (22 out of 39 students) recorded a 91% response rate with the same category. Comparative analysis between pretest and posttest results revealed a significant improvement in student learning outcomes. The learning completeness level before intervention only reached 18% ("incomplete"), but surged to 71% ("complete") after using the Quizizz media, demonstrating a 53% increase in learning outcomes. Thus, this study concludes that the development of interactive learning media using Quizizz is highly effective in supporting the improvement of student learning outcomes in PAI.